Russian neocorporatism as antineocorporate: urgent management problems - V. V. Tyan (Управление)
The problems of the genesis and practice of Russian neocorporatism in the conditions of the information revolution have considered in the article. Neocorporatism, formed in the last third of the twentieth century, is undergoing a serious test of modality at the beginning of the twenty-first century as a political and managerial concept. The moral aging of political ideas, doctrines, institutions is due to the nature of he development of society, the non-linear process of political modernization. Russian neokorporativizm (monosubject power (control) as anti-corporatism in practice passes the test of ethics. In the research of Russian neocorporatism the author is based on the analysis of political practice. In political science, the definitional problem of Russian neocorporatism has not yet solved. There is no clarity in the typological characteristic: democratic or bureaucratic? The author of the study considers Russian neocorporatism neotraditionalist. This conclusion is important for the analysis of domestic and foreign policy of the current government. The practice of Russian neocorporatism has highlighted the urgent problems of management. In the context of the information revolution and technological revolution, traditionalist and neotraditionalist methods of management lose their effectiveness. In the new realities, many of the principles of neo-corporatism are interpreted in the modern context and in their modality in political practice. The urgent management problems already can`t longer be solved by proven management methods in a changing environment. Scientific novelty of the research: solution of the definitional problem of non-corporatism, determination of the inertial nature of the management system functioning.